SISTEM PAKAR DIAGNONASA KERUSAKAN PADA HARDDISK MENGGUNAKAN METODE FORWARD CHAINING BERBASIS WEB - Sri Rama Putri; Muhamad Deden Firmansyah (CV. Multi Kreasi Media, 2024)
The rapid development of computer technology has led to an increase in the number of computer users worldwide. However, along with the growing number of computer users, hardware problems and computer malfunctions have become complex issues. These problems often arise due to factors such as the age of the device, unstable power supply, user errors, improper usage, and more. One of the frequently encountered hardware issues is related to the storage devices, specifically hard disk drives. Various symptoms can indicate a malfunctioning hard disk, which can disrupt the overall performance of the computer and its operating system. Typically, these issues become apparent during the initial booting process, where different sounds or error messages are displayed on the monitor to indicate the problem. Unfortunately, many computer users lack the necessary knowledge and skills to diagnose and repair such issues, resulting in unnecessary expenses when seeking professional assistance. To address these challenges, the development of an expert system capable of diagnosing hard disk failures becomes crucial. Such a system can assist less-experienced users in identifying and resolving hard disk issues, thereby saving them from unnecessary expenses and time spent consulting computer technicians. The proposed method for this expert system is forward chaining, a rule-based reasoning approach that helps in reaching conclusions or solutions. This research aims to develop a web-based expert system for diagnosing hard disk failures using the forward chaining method. The system is expected to provide accurate guidance and solutions to computer users experiencing hard disk problems while aiding technicians in efficiently addressing these issues.